Larynx Trauma and Hyoid Bone Fracture after Bite Injury in Dog: Case Report - Manchi, George; Brunnberg, Mathias M.; Shahid, Muhammad; Al Aiyan, Ahmad; Brunnberg, Leo; Stein, Silke (Frontiers in Veterinary Science, 2016)
An 8-year-old male Jack Russell crossbreed dog was admitted to our hospital with dyspnea and shock following a dog-bite injury on the ventral neck. Radiographs revealed subcutaneous emphysema and bilateral thyrohyoid bone fractures. Intraoperatively, rupture of both sternohyoid muscles, both hyoepiglotticus muscles, both thyrohyoid muscles, and a partial cranial rupture of the superficial sphincter colli muscle were detected. Part of the epiglottis was detached from the thyroid cartilage. The patient’s severed muscles and torn epiglottis were reattached using a simple interrupted suture pattern. Hyoepiglotticus muscles could not be identified. The bilateral thyrohyoid bone fractures were repaired with intraosseous wire suture. A temporary tracheostomy tube and an esophageal feeding tube were placed postoperatively. The dog was discharged after 8 days, re-examined at 2 and 6 months and laryngeal and pharyngeal function were evaluated as normal. To the authors’ knowledge, this is the first report of a dog that presented with laryngeal trauma with hyoid bone fracture and acute dyspnea that underwent surgical treatment resulting in an acceptable outcome.